The Gmina referendum in the local political conflict. The case of Wałbrzych - Glinka, Kamil (Journal of Education Culture and Society, 2020)
The Gmina referendum is one of the main institutions of direct democracy in Poland. Its procedure laid down in the act of 15th September 2000. The referendum is an expression of inhabitants’ commitment and their concern about the functioning of a local community, as well as serving its basic needs and interests. The analysis of the political conflict in Wałbrzych during 2010-2011 shows, however, that the voting may play a different role. The main aim of the article is to present the correlation between the gmina referendum from 2011 and the conflict in question. The intention of the author is to establish whether the referendum exerted a real impact on the course and the results of the conflict in Wałbrzych, and if so, to what extent. The time frame of the article lies between, on the one hand, the local government elections of 2010 preceded by the election campaign, and, on the other hand, the repeated elections for the President of Town and for the Town Council of 2011.